Optimizing the concrete strength of lightweight concrete containing nano palm oil fuel ash and palm oil clinker using response surface method - Hamada, Hussein Mahmood; Al-Attar, Alyaa A.; Tayeh, Bassam; Fadzil, Mat Yahaya (Elsevier Ltd, 2022)
Lightweight aggregate concrete (LWAC) has gradually gained popularity as a significant material in the concrete industry worldwide. One of the important lightweight aggregates is palm oil clinker (POC). Moreover, palm oil fuel ash (POFA) can be used as a partial cement replacement in concrete. This paper presents a study in which POFA of Nano-particle size was used to enhance the lower performance of LWAC made with POC aggregate. The Nano-POFA (NPOFA) was used as cement replacement of 0%, 10%, 20%, and 30% and POC aggregate was used as coarse aggregate at replacement levels of 0%, 50%, and 100%. Flexural and split tensile strengths and ultrasonic pulse velocity (UPV) were investigated for different concrete mixtures. For optimizing the parameters of the mix design, the response surface method (RSM) was adopted, and within it, a central composite design (CCD) approach was used. The results show that the interaction of POC and NPOFA affects the responses (UPV, flexural and tensile strengths). However, the POC tends to decrease all the responses. Whereas, the NPOFA tends to increase it especially at later ages. The highest UPV, flexural and split tensile strengths were observed for mixture (M7) that were 4375 m/s, 8.53 MPa, and 5.38 MPa, respectively. It can be concluded that the optimization method by RSM is an active way to enhance the mix design of LWAC.